Modified ashay algorithm for finding all the cliques a connected network - Nur Farah Ain Mislan, 1989-; Shaharuddin Salleh, supervisor; Fakulti Sains (2013)
Tesis Sarjana Saina (Matematik)) - Universiti Teknologi Malaysia, 2013